2011
DOI: 10.5603/fhc.2011.0015
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular abnormalities in capillaroscopy correlate with higher serum IL-18 and sE-selectin levels in patients with type 1 diabetes complicated by microangiopathy

Abstract: Microvascular abnormalities are one of the most important causes of persistent diabetic complications. The aim of this study was to compare microvascular changes examined by nailfold capillaroscopy with serum concentrations of soluble E-selectin (sE-selectin) and IL-18 in type 1 diabetic patients with and without microangiopathy. Serum levels of sE-selectin and IL-18 were determined by an enzyme-linked immunosorbent assay in 106 patients with type 1 diabetes and in 40 healthy controls. All diabetic patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 19 publications
3
30
0
2
Order By: Relevance
“…In consistence to other investigations [3] [17], we saw a high frequency of capillary changes especially increased tortuosity of vascular loops and angiogenesis in diabetic patients. Kaminska-Winciorek et al also showed an increased frequency of twisted capillaries in patients with diabetes type 1 and 2 [4].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In consistence to other investigations [3] [17], we saw a high frequency of capillary changes especially increased tortuosity of vascular loops and angiogenesis in diabetic patients. Kaminska-Winciorek et al also showed an increased frequency of twisted capillaries in patients with diabetes type 1 and 2 [4].…”
Section: Discussionmentioning
confidence: 82%
“…Vascular damage, finally leads to eventual capillary obliteration. Morphological and functional changes in capillary microscopy have been reported in relation to vascular reactivity after induced ischemia [1]- [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher serum levels of sE-selectin and IL-18 were demonstrated in diabetic patients compared to controls. Significant differences of sE-selectin and IL-18 serum concentrations were observed between diabetic patients with microangiopathy and controls suggest that abnormalities in nailfold capillaroscopy may reflect the extent of microvascular involvement and are associated with higher sE-selectin and IL-18 serum levels, as well as with microangiopathic complications in diabetic patients (Kuryliszyn et al, 2011). Hyper glycaemia increases inflammatory cytokine concentration in the blood.…”
Section: Il-18 Enhances Angiogenesismentioning
confidence: 91%